Pain, numbness, or both? Distinguishing the longitudinal course and predictors of positive, painful neuropathic features vs numbness after breast cancer surgery. (22nd November 2021) - Flowers, K. Mikayla; Beck, Meghan; Colebaugh, Carin; Haroutounian, Simon; Edwards, Robert R.; Schreiber, Kristin L.
Abstract : Supplemental Digital Content is Available in the Text. Examining the divergence of prevalence and predictors of postsurgical numbness vs positive neuropathic symptoms gives insights into variation in clinical postoperative pain experienced by patients. Abstract : Introduction: Both positive (burning, stabbing, and allodynia) and negative (numbness) neuropathic symptoms may arise after surgery but likely contribute differently to patients' postoperative pain experience. Numbness has been identified as divergent from positive neuropathic symptoms and therefore excluded from some neuropathic assessment tools (Neuropathic Pain Scale for PostSurgical patients [NeuPPS]). Objectives: In this prospective longitudinal study of patients undergoing breast surgery, we aimed to delineate the time course of numbness and its coincidence with NeuPPS and to contrast the association of surgical, psychosocial, and psychophysical predictors with the development of negative vs positive neuropathic symptoms. Methods: Patients reported surgical area sensory disturbances at 2 weeks and 3, 6, and 12 months postoperatively. Association of baseline demographic, surgical, psychosocial, and psychophysical factors with NeuPPS and numbness across time was investigated using generalized estimating equation linear and logistic regression. Results: Numbness was consistently reported by 65% of patients; positive neuropathic symptoms were less common, often decreasing over time. Neuropathic Pain scale for PostSurgical patients and numbness co-occurred in half of patients and were both associated with greater clinical pain severity and impact, younger age, axillary surgery, and psychosocial factors. More extensive surgery and chemotherapy were only associated with numbness. Conversely, other chronic pain, lower physical activity, perioperative opioid use, negative affect, and lower baseline pressure pain threshold and tolerance were only associated with NeuPPS. Patients reporting numbness alone did not endorse substantial clinical pain. Conclusions: Differentiation of predictors, prevalence, and time course of numbness vs NeuPPS in breast surgical patients revealed important distinctions, suggesting that their independent assessment is worthwhile in future studies of postsurgical pain.